Northrop Frye and the poetics of process - Cotrupi, Caterina Nella, 1953- (University of Toronto Press, 2000)
Challenging the dismissive view of Frye's work as closed and outdated, Cotrupi explores the implications of his proposition that the history of criticism may be seen as having two main approaches - literature as ""product"" and literature as ""process.""